2023
DOI: 10.1002/slct.202300362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blueberry and Dandelion Aqueous Extracts in the Synthesis of Gold and Silver Nanostructures, and Their Applications as Anti‐Pseudomonas aeruginosa Agent

Abstract: We performed a comparative study using aqueous extracts of dandelion flowers and blueberry fruits to synthesize gold‐ (Au) and silver‐ (Ag) nanostructures (NSs). The blueberry extracts gave nanowire and spherical AuNSs upon changing the ratio of the extracts to Au3+precursor while altering the ratio for the dandelion extracts resulted in formation of only anisotropic AuNSs. Similar results were obtained during the AgNSs, where the dandelion extracts resulted in formation of quasi‐spherical AgNSs at the tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…We also performed a linear regression analysis for the tested 37 phytochemicals, total phenolic, total flavonoid, reducing carbohydrate and protein amounts. Based on a previous study, it was observed that most concentrated phenolics and most concentrated flavonoids play the key roles in determining the shape and morphology of the AuNSs [54] . Therefore, the sum of the most concentrated phenolic acids was divided into the sum of the most concentrated flavonoids and multiplied with the ratio of total phenolic to total flavonoid.…”
Section: Results and Disucussionsmentioning
confidence: 99%
“…We also performed a linear regression analysis for the tested 37 phytochemicals, total phenolic, total flavonoid, reducing carbohydrate and protein amounts. Based on a previous study, it was observed that most concentrated phenolics and most concentrated flavonoids play the key roles in determining the shape and morphology of the AuNSs [54] . Therefore, the sum of the most concentrated phenolic acids was divided into the sum of the most concentrated flavonoids and multiplied with the ratio of total phenolic to total flavonoid.…”
Section: Results and Disucussionsmentioning
confidence: 99%